Cyclin D1 Stability Is Partly Controlled by O-GlcNAcylation - Masclef, Louis; Dehennaut, Vanessa; Mortuaire, Marlène; Schulz, Céline; Leturcq, Maïté; Lefebvre, Tony; Vercoutter-Edouart, Anne-Sophie (Frontiers in Endocrinology, 2019)
Cyclin D1 is the regulatory partner of the cyclin-dependent kinases (CDKs) CDK4 or CDK6. Once associated and activated, the cyclin D1/CDK complexes drive the cell cycle entry and G1 phase progression in response to extracellular signals. To ensure their timely and accurate activation during cell cycle progression, cyclin D1 turnover is finely controlled by phosphorylation and ubiquitination. Here we show that the dynamic and reversible O-linked β-N-Acetyl-glucosaminylation (O-GlcNAcylation) regulates also cyclin D1 half-life. High O-GlcNAc levels increase the stability of cyclin D1, while reduction of O-GlcNAcylation strongly decreases it. Moreover, elevation of O-GlcNAc levels through O-GlcNAcase (OGA) inhibition significantly slows down the ubiquitination of cyclin D1. Finally, biochemical and cell imaging experiments in human cancer cells reveal that the O-GlcNAc transferase (OGT) binds to and glycosylates cyclin D1. We conclude that O-GlcNAcylation promotes the stability of cyclin D1 through modulating its ubiquitination.